Toughness Differentiation of Welded Low Carbon Steel By Using Baked Low Hydrogen Electrode (E7018) and Low Hydrogen Electrode Without Baking Process - Prasetya Didi Rahman; Jasman Jasman; Nofri Helmi (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2019)
Low hydrogen electrode known as lime type, due lime ferritic or lime flourspar countain. This electrode produce low hydrogen weld metal, which can dissolve weld metal from embrittlement and or cracking, the coating developed to contain low amount of moisture so storage handling should be carefully, unused electrode must rebaked at temperatures between 260-425ºC for 2-6 hours. This research purpose to know imfluence of toughness welding result by using baked low hydrogen electrode on low carbon steel. This research using experimental method, 12 speciment divided into 4 groups specimen, specimen A welded by using electrode without baking process, specimen B welded by using baked electrode at 260ºC, specimen C welded by using baked electrode at 343ºC and spesimen D welded by using baked electrode at 435ºC. After the test obtained the average potential energy amount 65,8107 Nm and average impact amont 0,81539x106 N/m from spesimen A, spesimen B obtain average potential energy amount 81,9396 Nm and average impact amount 1,00251x106 N/m, spesimen C obtain average potential energy amount 126,3913 Nm and average impact amount 1,56703x106 N/m, and spesimen D obtain average potential energy amount 92,5795 Nm and average impact amount 1,13445x106 N/m. The most tough specimen in C group, with average potential energy amount 126,3913 Nm and average impact amount 1,56703x106 N/m.